Changes in clinical features and seasonal variations of Crohn’s disease at diagnosis: a 10-year observational study in China - Deng, Jun; Lu, Yi; Liu, Tao; Zhang, Min; Yao, Jia-yin; Zhi, Min (Frontiers in Medicine, 2024)
The clinical aspects of Crohn's disease (CD) at diagnosis determine its therapy and management. The onset of CD follows a seasonal pattern. We aimed to analyze changes in the clinical features and seasonal variations of newly CD patients over the last decade.CD patients were divided into cohort 1 (2012-2016) and cohort 2 (2017-2021). The clinical characteristics were collected and the trends according to the year and season of diagnosis were analyzed.A total of 2038 patients were included. Cohort 1 had a considerably greater proportion of diarrhea, fever, hematochezia, weight loss and extraintestinal manifestations. The levels of platelet and Creactive protein were higher in cohort 2 patients, but the opposite was true for albumin levels (P＜ 0.05). The rate of increased eosinophils, increased gangliocyte and abundant lymphoplasmacytic infiltrate significantly decreased over the years. Patients with granulomas were diagnosed with CD at an earlier age (P=0.006). Cohort 1 patients used more conventional drugs, while cohort 2 patients apply more biologics (P＜0.05). The diagnosis occurred more frequently in summer and less frequently in winter. Patients diagnosed in winter had notably higher BMI, lower frequency of perianal disease and lowest incidence of asthenia and weight loss.The clinical phenotype, laboratory and pathological characteristics of CD has changed over time in China. The diagnosis of CD tends to have a seasonal trend with the highest incidence in summer. CD patients diagnosed in winter appear to have a milder form of the disease.